Effect of Different EM4 Dosage in Walne on the Laboratory-scaled Chlorella sp. Culture - Jelita Widya Mustika; Waluyo Waluyo; Shobrina Silmi Qori Tartila (JURNAL AKUAKULTURA, 2026)
This study aims to analyze the effect and optimal dosage of EM4 and Walne on the abundance, growth rate, water quality, and biomass of Chlorella sp. EM4 was administered in three doses (1 ml, 2 ml, and 3 ml) with the addition of 1 ml Walne in each treatment, while the control was only given 1 ml Walne. The Completely Randomized Design (CRD) method was used with three replications per treatment. The results showed no significant differences between treatments, with the highest abundance in the control (1 ml Walne). This indicates that the combination of EM4 and Walne is less effective in increasing the productivity of Chlorella sp. However, biomass did not show significant differences between treatments, indicating that the two ingredients do not drastically affect the final result. In addition to being a natural feed, Chlorella sp. has the potential to be developed in the field of renewable energy, such as biofuel, due to its high lipid content. This finding opens up opportunities for further research to optimize microalgae culture media with more efficient alternative materials. In conclusion, although EM4 and Walne did not have a significant impact, exploration of the use of Chlorella sp. outside the aquaculture sector needs to be continued.